A Cartesian grid based multiphase flow model for water impact of an arbitrary complex body. (January 2019) - Shi, Fulong; Xin, Jianjian; Jin, Qiu
Highlights: A radial basis function ghost cell method (RBFGCM) is developed to treat the arbitrary moving body on a fixed Cartesian grid. A distance function assignment method is developed to treat the contact boundary condition between the free surface and the solid boundary. We are the first to extend the GALS method to simulate wave-structure interaction problems. The results show that the present method can more accurately predict the slamming load in the presence of flow separation and air cushion than the smoothed particle hydrodynamics (SPH) based single-phase flow model and the boundary element method (BEM). Abstract: A Cartesian grid based multiphase flow model is developed to simulate water impact problems. This model is capable of simulating complex moving bodies interacting with a highly non-linear free surface such as jet flow or air cushion. A radial basis function based ghost cell method (RBFGCM) is developed to treat the arbitrary moving body on a fixed Cartesian grid. The complex moving boundary is tracked with the RBF and ghost cells are identified based on the signed function property of the RBF. To capture large deformation of the free surface, a gradient-augmented level set (GALS) method is used. Sub-grid resolution is obtained by simultaneously evolving both the level set (LS) function and its gradient information. Also, a simple distance function assignment method is developed to treat the contact boundary between the free surface and the solid surface. The accuracies of the ghost cell method (GCM) and the GALS method are validated by inline oscillation of a cylinder and horizontal sloshing cases, respectively. Then, the water impact of an arbitrary body is simulated. The cases include the water entry of a free falling multihull and the water entry of a bow-flare ship section with various roll angles. The accuracy of the proposed multiphase flow model and its capability are examined by comparing the present results to experimental and numerical results. Also, the results show that the present method can more accurately predict the slamming load in the presence of flow separation and air cushion than the smoothed particle hydrodynamics (SPH) based single-phase flow model and the boundary element method (BEM). Furthermore, the influence of roll angles on the slamming load and the free surface are studied.